Performance of real estate investment trust (REITs) after global economy crises in Malaysia - Phoo, Kho Jing; Humaida Banu Samsudin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Real Estate Investment Trusts (REITs) is a trust unit that creates fund flow from investors and unit holders to real estates. In Malaysia, REITs is a low-risk investment instrument. It can provide at least 90 percent of net profit to the investors and unit holder in terms of dividend. The aim of this study is to examine the performance of REITs Malaysia compared to market benchmark, FTSE Bursa Malaysia Kuala Lumpur Composite Index (FBM KLCI) after economy crises. The crises are Global Financial Crisis (2008), European Debt Crisis (2011) and Crude Oil Price Crash (2014). Three risk-adjusted measurements are used to test the performance of REITs, which are Sharpe ratio, Treynor ratio and Jensen’s alpha. The result of this study will give an overall idea to investors on the performance of REITs Malaysia against risks.